Selfitis: An Analysis on Prevalence and Attitude among College Students - MG Sreejamol; R Radhika; Rajalakshmi Reghuvaran (Indian Journal of Psychiatric Nursing)
Introduction: Our daily lives now mostly revolve around our smartphones. Due to the widespread use of mobile phones, selfies have become the newest technical trend among young people. The most common practice of taking selfies in dangerous situations is proving to be a fatal one. The majority of these fatalities and injuries are from falls from great heights and posing with dangerous objects. Objective of the Study: The objective of this study was to assess the attitude and prevalence of selfitis among college students. Methodology: Descriptive design was used in this study. Convenience sampling technique was used to select 400 college students from a technical college of Ernakulam district, Kerala, within the age group of 16–24 years. The data were collected using two semi-structured questionnaires and Solanki Selfie Addiction Scale, a standardized tool for the assessment of selfie addiction. Results: It was found that 86% (344) were males and 14% (56) were females. Eighty-five percentage (340) of the study subjects had smartphone and only a few, 60 (15%) were not using it. About 59.5% (238) of them used all the enlisted social media. The prevalence of selfie addiction shows majority, 260 (65%) had mild selfie addiction, 76 (19%) had no selfie addiction but few had moderate 64 (16%) selfie addiction, and there was no severe selfie addiction. Result of attitude shows that 82% (328) have a neutral attitude, 16% (64) shows a positive attitude, and 2% (8) shows a negative attitude toward selfie. Conclusion: The result highlights the importance of providing education regarding the healthy use of social media.